Involvement and Challenges of School Guidance and Counselling Teacher Towards Special Needs Students - Norafifah Bali; Mohamad Hashim Othman (Asian Social Work Journal, 2017)
Implementation of guidance and counselling services in schools requires School Guidance and Counselling Teachers (SGCT) to provide this services to all students, whether the mainstream students or Special Needs Students (SNT), as outlined in the Buku Rekod Perkhidmatan Bimbingan dan Kaunseling (Guidance and Counselling Services Record Book). This situation has challenged SGCT especially in meeting the specific needs of SNT. This raises questions regarding the involvement of SGCT in providing guidance and counselling services especially to SNT as well as challenges faced in implementing such services. Therefore, a qualitative study has been conducted to answer the questions. This study involved six SGCT who serve in schools that adopt the Integrated Special Education Program or the Inclusive Education Program. Semi-structured interview questions have been used to obtain relevant information. The finding of this study shows that there are direct and indirect SGCT's involvements with SNT. While the challenges that GBKS face in carrying out guidance and counselling services are divided into three themes, namely the challenges characterized by SGCT, challenges characterized by SNT and challenges characterized by the Organization. The findings of this study can provide information on the implementation of guidance and counselling services to SNT and can be used as an improvement of the existing guidelines to increase the involvement of SGCT in providing guidance and counselling services especially to SNT.